(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
An image created using oil paints can compare favorably with other means of imagery. This is because oil paints dissolve in the oil and create a smooth, consistent image that can be more resistant to safety and durability. One of the important characteristics of oil paint is the ability to mix base colors, which allows artists to create an infinite number of shades. And also when mixing paints with some substances, you can get additional different color shades and get a more effective and convenient paint texture for use on various surfaces.